Development of a Bidirectional Dc/Dc Converter with Dual-Battery Energy Storage for Hybrid Electric Vehicle System - G. Venkata Subbaiah, Vijay Karamala, N. P. Subramaniyam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Hybrid electric vehicles (HEVs) offer many benefits, such as high fuel efficiency, reduced emissions, and noisy service. Two or three frequency buses are available in HEVs for various operating purposes. There are requirements of an electrochemical ally independent continuously variable DC-DC converter to connect separate DC voltage bus and pass energy back backward and forwards. In this report a battery connected induction motor drive is proposed with charging and discharging capabilities converter in motoring mode and ergative breaking mode. Three bidirectional switches are used to charge and discharge the batteries connected in the topology. The topology consists of two batteries with different voltage levels, one at 96V and other at 48V which discharge or charge with respect to the reference value given in the controller. The controller is a PI gain controller which calculates the duty ratio for the switches connected in the converter. A PWM pulse is generated at very high frequency for the switches at diffent modes run using MATLAB Simulink software. The output voltage from the converter is used to run an induction motor and charteristics of the machine are observed by graphs generated with respect to time. All of the critical specifications for DC-DC converters for electric and hybrid vehicles are high performance, small size, lightweight and durability.